Effects of Chat GPT Assisted Learning Technique on Upper Basic II Students’ Interest and Achievement in Social Studies in Jos North, Plateau State, Nigeria - Shittu Lukman Olayinka; Sunday Jacob; Dauda A. Ariya (Matondang Journal, 2025)
This study investigated the effects of ChatGPT-assisted learning on upper basic II students’ interest and achievement in Social Studies in Jos North, Plateau State, Nigeria. The research addressed three research questions and tested one null hypothesis at a 0.05 level of significance. Guided by Lev Vygotsky’s Constructivist Learning Theory, which emphasizes active student participation, the study adopted a quasi-experimental research design. The population comprised 1,230 upper basic II students from 22 public schools in Jos North Local Government Area, from which a sample of 133 students was drawn. Two schools were randomly selected, with one assigned as the experimental group and the other as the control group. Two researcher-developed instruments were used for data collection: the Social Studies Interest Questionnaire (SSIQ) and the Social Studies Achievement Test (SSAT). Both instruments were validated for content and reliability, with reliability coefficients established through the test-retest method. Data were analyzed using descriptive and inferential statistics. Findings revealed that students exposed to the ChatGPT-assisted learning technique showed significantly greater gains in both interest and achievement compared to those taught via conventional methods. The study concluded that ChatGPT-assisted learning is effective in enhancing students’ interest and achievement in Social Studies at the upper basic level. It recommended that educational institutions implement training programs to prepare teachers and students for the effective and ethical use of ChatGPT in classrooms.